1989
DOI: 10.1002/j.1537-2197.1989.tb15124.x
|View full text |Cite
|
Sign up to set email alerts
|

Influence of the Pistil on Pollen Tube Kinetics in Peach (Prunus Persica)

Abstract: Pollen tube growth has been studied in peach and has been related to changes in the pistil structures which the pollen tube has to traverse in its way from the stigma down to the ovule. Growth of the pollen tubes along the pistil is not continuous. While pollen tubes reach the base of the style 7 days after pollination, fertilization does not take place until 12 days later. Pollen tubes stop for 5 days at the top of the obturator and they further stop for 3 days before entering the ovule. The pollen tube growt… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
22
0
8

Year Published

1991
1991
2003
2003

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 89 publications
(32 citation statements)
references
References 31 publications
2
22
0
8
Order By: Relevance
“…On the placental surface of the peach, alterations in pollen tube growth were first seen associated with the obturator (Arbeloa & Herrero 1987), which strongly suggested that a secretion by this structure was required for the pollen tube to progress. Further, in plants where a delayed penetration of the ovule was recorded (Herrero & Arbeloa 1989), it was later discovered that the delay coincided precisely with the time required for the ovules to produce a secretion at the exostome and micropyle (Herrero 2000).…”
Section: Alterations In Pollen Tube Development and Male-female Asyncmentioning
confidence: 95%
See 1 more Smart Citation
“…On the placental surface of the peach, alterations in pollen tube growth were first seen associated with the obturator (Arbeloa & Herrero 1987), which strongly suggested that a secretion by this structure was required for the pollen tube to progress. Further, in plants where a delayed penetration of the ovule was recorded (Herrero & Arbeloa 1989), it was later discovered that the delay coincided precisely with the time required for the ovules to produce a secretion at the exostome and micropyle (Herrero 2000).…”
Section: Alterations In Pollen Tube Development and Male-female Asyncmentioning
confidence: 95%
“…The timing of these events is crucial for, far from been a passive structure, the pistil continues to develop along a pathway that can both favour and discourage growth of the pollen tube. This is particularly apparent in the ovary, which owing to the basipetal maturation of the pistil (Herrero & Arbeloa 1989), develops last. Of course, the pollen tube itself is following its own developmental pathway as it passes through the stigma and into the ovary, and the synchrony of these parallel pathways is clearly a key to successful fertilization and seed formation.…”
Section: Introductionmentioning
confidence: 99%
“…The pollen-style and pollen-pollen interactions are known to play an important role in the reproductive success of single male gametophytes (Sari-Gorla et al, 1976;Ottaviano & Sari-Gorla, 1979; Sari- Gorla & Rovida, 1980;Herrero & Arbeloa, 1989), and are expected to operate in natural populations.…”
Section: Dscussonmentioning
confidence: 99%
“…The most comprehensive analysis of the genetic control of pollen fitness components was carried out in maize (Ottaviano et a!., 1988): grain germinability and tube growth revealed a large amount of variability and high heritability; a signi-ficant response to gametophytic selection for tube growth rate and a correlated response for sporophytic traits were detected, proving genetic overlap in the control of the pollen tube growth and the vigour of sporophytic tissues. Moreover, the fertilization ability of a given pollen genotype is modulated by intergametophytic effects (Sari-Gorla & Rovida, 1980), by environmental effects (Young, 1992) and by interactions with the stylar tissue (Pfahler, 1967;HeslopHarrison, 1975;Sari-Gorla et a!., 1976;Herrero & Arbeloa, 1989).…”
mentioning
confidence: 99%
“…In peach, pollen tube growth has been related to changes in the pistil structures which the pollen tube has to pass through on its way from the stigma to the ovule: starch, present all along the stylar tract at anthesis, vanishes as the pollen tubes pass by, indicating that the pollen tube growth is heterotrophic (Herrero & Arbeloa, 1989).…”
Section: Introductionmentioning
confidence: 99%